Recent Advances in the Pathophysiology of Fatty Acid Oxidation Defects: Secondary Alterations of Bioenergetics and Mitochondrial Calcium Homeostasis Caused by the Accumulating Fatty Acids - Amaral, Alexandre Umpierrez; Wajner, Moacir (Frontiers in Genetics, 2020)
Deficiencies of medium-chain acyl-CoA dehydrogenase (MCAD), mitochondrial trifunctional protein (MTP), isolated long-chain 3-hydroxyacyl-CoA dehydrogenase (LCHAD) and very long-chain acyl-CoA dehydrogenase (VLCAD) activities are considered the most frequent fatty acid oxidation defects (FAOD). They are biochemically characterized by accumulation of medium-chain, long-chain hydroxyl and long-chain fatty acids and derivatives, respectively, in tissues and biological fluids of the affected patients. Clinical manifestations commonly include hypoglycemia, cardiomyopathy and recurrent rhabdomyolysis. Although the pathogenesis of these diseases is still poorly understood, energy deprivation secondary to blockage of fatty acid degradation seems to play an important role. However, recent evidence indicates that the predominant fatty acids accumulating in these disorders disrupt mitochondrial functions and are involved in their pathophysiology possibly explaining the lactic acidosis, mitochondrial morphological alterations and altered mitochondrial biochemical parameters found in tissues and cultured fibroblasts from some affected patients and also in animal models of these diseases. In this review we will update the present knowledge on disturbances of mitochondrial bioenergetics, calcium homeostasis, uncoupling of oxidative phosphorylation and mitochondrial permeability transition induction provoked by the major fatty acids accumulating in prevalent FAOD. It is emphasized that further in vivo studies carried out in tissues from affected patients and from animal genetic models of these disorders are necessary to confirm the present evidence mostly achieved from in vitro experiments.